Continuous dependence on parameters - Afonso, Suzete M. [UNESP]; Bonotto, Everaldo M.; Federson, Márcia; Mesquita, Jaqueline G. (Wiley, 2021)
This chapter aims to investigate the results on continuous dependence on parameters for generalized ordinary differential equations (ODEs) taking values in a Banach space. It includes a new result on the convergence of solutions of a nonautonomous generalized ODE. The chapter also investigates continuous dependence results on parameters for generalized ODEs in a Banach space X, equipped with norm ‖. It presents a result on continuous dependence of solutions on parameters for generalized ODEs. The chapter also aims to prove some results on continuous dependence on parameters for measure functional differential equations (FDEs), and the correspondence between generalized ODEs and measure FDEs.
Keywords: Banach space; Continuous dependence; Functional differential equations; Ordinary differential equations